2022
DOI: 10.3310/irwi5180
|View full text |Cite
|
Sign up to set email alerts
|

Early computed tomography coronary angiography in adults presenting with suspected acute coronary syndrome: the RAPID-CTCA RCT

Abstract: Background Acute coronary syndrome is a common medical emergency. The optimal strategy to investigate patients who are at intermediate risk of acute coronary syndrome has not been fully determined. Objective To investigate the role of early computed tomography coronary angiography in the investigation and treatment of adults presenting with suspected acute coronary syndrome. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Then, 29 studies were excluded because of lack of intervention or control arm; duplicated reports of the same research; incorrect study design (eg, not randomized); lack of relevant outcome; publication reporting only the study design; or because it was a review, editorial, commentary, or abstract. Finally, 22 RCTs ( 10 12 , 17 19 , 21 36 ) were included in the final analysis, representing a total of 9379 participants, with 4956 participants assigned to the CCTA arms and 4423 participants assigned to the SOC arms. The follow-up length ranged from 28 days to more than 5 years among studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, 29 studies were excluded because of lack of intervention or control arm; duplicated reports of the same research; incorrect study design (eg, not randomized); lack of relevant outcome; publication reporting only the study design; or because it was a review, editorial, commentary, or abstract. Finally, 22 RCTs ( 10 12 , 17 19 , 21 36 ) were included in the final analysis, representing a total of 9379 participants, with 4956 participants assigned to the CCTA arms and 4423 participants assigned to the SOC arms. The follow-up length ranged from 28 days to more than 5 years among studies.…”
Section: Resultsmentioning
confidence: 99%
“…This is supported by our findings which revealed no evidence of a difference in LOS between CCTA and SOC arms in studies containing greater than or equal to 10% of high-risk participants. Of note, one of the studies in this group ( 12 ) randomized participants during their original visit at the ED, hospital, or cardiology unit but allowed CCTA to be performed either during that visit or after discharge within 72 hours of randomization. This study revealed a 10% increase in the LOS for the CCTA arm (95% CI: 0%, 21%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 The RAPID-CTCA RCT study investigated the role of early CCTA in patients presenting to the ED for chest pain and suspected ACS, and failed to demonstrate a significant reduction of the revascularization rates, ACS therapies, or preventative therapies at discharge following early CCTA in patients with elevated cTn. 25 This underlines the superiority of cTn as a first-line diagnostic test for triage of patients with suspected ACS in the ED, elevated cTn levels being sufficient for establishing the diagnosis in the absence of other expensive techniques.…”
Section: Ccta and Cardiac Biomarkers In The Edmentioning
confidence: 89%